Financing Constraints and Inventory Investment: A Comparative Study with High-Frequency Panel Data - Carpenter, Robert E.; Fazzari, Steven M.; Petersen, Bruce C. (The Review of Economics and Statistics, 1998)
This study provides new evidence of the importance of financing constraints for explaining the dramatic cycles in inventory investment. We compare the empirical performance of different financial variables (coverage ratio, cash stocks, and cash flow) used in previous research to test for the presence of financing constraints. The comparison is undertaken in a common framework with an identical sample and high-frequency (quarterly) firm panel data. Cash flow is much more successful than cash stocks or coverage in explaining the facts about inventory investment across firm size, different inventory cycles, and different manufacturing sectors.